2008
DOI: 10.1177/230949900801600109
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Hip Screw and Compression Plate Fixation of Ipsilateral Femoral Neck and Shaft Fractures

Abstract: Purpose. To evaluate surgical outcomes of ipsilateral femoral neck and shaft fractures. Methods. Between April 1997 and September 2004, 29 men and 8 women (mean age, 37 years) underwent fixation of femoral neck and shaft fractures using a dynamic compression plate plus a dynamic hip screw or screws. There were 30 femoral neck and 7 pertrochanteric fractures. Functional results were assessed according to the Friedman and Wyman classification. Results. The mean follow-up period was 49 months. Of the femoral neck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 15 publications
3
22
0
Order By: Relevance
“…There are several studies that have found excellent results with the use of 2 implants for the femoral neck-shaft combination. 10,19,[27][28][29][30] Our study had several limitations, including the fact that it was retrospective in nature and that multiple surgeons with different levels of experience were included. Because of the nature of this multicenter review, there was no protocol for routine CT scanning of high-energy femoral shaft fractures and no routine protocol for operative management of these fractures.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies that have found excellent results with the use of 2 implants for the femoral neck-shaft combination. 10,19,[27][28][29][30] Our study had several limitations, including the fact that it was retrospective in nature and that multiple surgeons with different levels of experience were included. Because of the nature of this multicenter review, there was no protocol for routine CT scanning of high-energy femoral shaft fractures and no routine protocol for operative management of these fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Frequently, combination of fixation was used for these patients. 7,4,8,1 However, there is less frequent report that ipsilateral subtrochanteric, supracondylar, and intercondylar fractures are treated by femoral lock plant alone. The purposes of this case study report femoral lock plant alone was used for ipsilateral subtrochanteric, supracondylar, and intercondylar fracture.…”
Section: Introductionmentioning
confidence: 96%
“…These injuries often result from high energy mechanism after a motorcycle–car collision in traffic road accidents or falling from height 3, 4, 5. Moreover, the questions about management, therapeutical difficulty concerning implants choice, order of injury management and time of surgical management are unknown.…”
Section: Introductionmentioning
confidence: 99%